Karakteristik Pasien Meningioma di RSUD Ulin Banjarmasin Tahun 2018-2020 - Faradila Hayuning Raharjanti; Agus Suhendar; Fakhrurrazy Fakhrurrazy; Ardik Lahdimawan; Istiana Istiana (Homeostasis, 2022)
Abstract: Meningioma are the most common primary tumors in the CNS. Although these tumors are benign, meningioma are a frequent cause of morbidity. This study aims to determine the characteristics of meningioma patients at General Ulin Hospital Banjarmasin in 2018-2020. This study used a retrospective descriptive method from the patient's medical record. The results of this study show that the number of meningioma patients in 2018 was 38 patients (40.4%), in 2019 was 42 patients (44.7%) and in 2020 was 14 patients (14.9%). The most common characteristics were 46-55 range of age (38.3%), female (84%), South Kalimantan (90.4%), Islam (96.8%), private employees (28.7%), BPJS patients (93.6%). All patients had no family history of the disease. Only one patient was recorded as having a history of hormonal treatment (1.1%). Most of the patients had no history of allergies (89.4%). Six patients were classified as class I meningioma (6.4%). The most common tumor location was supratentorial (89.3%). The most common tumor size occurred in the diameter range of 3-6 cm (33%). The most common clinical symptom that appeared was headache (57.4%). GCS scores pre and post operative the most, including mild-normal. The length of treatment for the most patients was more or equal to 10 days (54.3%). The most patient’s outcome was recovered (90.4%). Keywords: Meningioma, characteristics Abstrak: Meningioma adalah tumor primer tersering di SSP. Meskipun tumor ini bersifat jinak, meningioma sering menjadi penyebab morbiditas. Penelitian ini bertujuan untuk mengetahui karakteristik pasien meningioma di RSUD Ulin Banjarmasin tahun 2018-2020. Penelitian ini menggunakan metode deskriptif retrospektif dari rekam medis pasien. Hasil penelitian ini menunjukkan jumlah pasien meningioma terbanyak terjadi tahun 2019 sebanyak 42 pasien (44,7%). Karakteristik terbanyak terjadi pada rentang usia 46-55 tahun (38,3%), jenis kelamin perempuan (84%), alamat asal Kalimantan Selatan (90,4%), agama Islam (96,8%), pekerjaan pegawai swasta (28,7%) dan jaminan kesehatan berupa BPJS (93,6%). Semua pasien tidak memiliki riwayat keluarga. Sebagian besar pasien tidak memiliki riwayat alergi (89,4%). Lokasi tumor terbanyak di supratentorial (89,3%). Ukuran tumor terbanyak adalah diameter 3-6 cm (33%). Gejala klinis terbanyak adalah nyeri kepala (57,4%). Skor GCS datang dan pulang terbanyak termasuk ringan-normal. Lama perawatan pasien terbanyak adalah ≥10 hari (54,3%). Luaran terbanyak adalah sembuh (90,4%). Kesimpulan penelitian ini adalah karakteristik terbanyak pasien meningioma terjadi pada rentang usia 46-55 tahun, jenis kelamin perempuan, alamat asal Kalimantan Selatan, agama Islam, pekerjaan pegawai swasta, pasien BPJS, tidak ada riwayat penyakit keluarga, lokasi tumor supratentorial, diameter 3-6 cm, gejala nyeri kepala, skor GCS ringan-normal, lama perawatan ≥10 hari, dan luaran terbanyak sembuh. Kata-kata kunci: karakteristik, meningioma